IMPLEMENTASI DAKWAH BERBASIS KELUARGA:Pengembangan Ekosistem Marhamah sebagai Fondasi Peradaban Islam - Yuyun Yuningsih; Tata Sukayat; Ridwan Rustandi (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
Family-based daʿwah represents a foundational yet undertheorized dimension of Islamic mission studies. This study investigates how Muslim families in urban Bandung, Indonesia, implement family-based daʿwah to cultivate a marhamah (compassion-based) ecosystem through their everyday practices. Employing Alfred Schutz's interpretive phenomenological analysis, this study conducted in-depth interviews, participatory observation, and documentation with twenty purposively selected Muslim families meeting criteria of marriage duration, child-rearing stage, and active daʿwah engagement. Four interrelated themes emerged: (1) internalization of Qur'anic values in domestic contexts; (2) affective function as the relational infrastructure of marhamah; (3) dialogic and exemplary daʿwah communication practices; and (4) the social radiation of family-formed compassion values into the wider community. These findings challenge prior studies that position the family primarily as a normative unit of Islamic law, by demonstrating that the family operates as a dynamic agent of daʿwah-driven social transformation. The study introduces the 'marhamah ecosystem' as a new analytical framework integrating Islamic theology, communication theory, and family sociology within the field of daʿwah studies ('ilm al-da'wah). Practical implications are drawn for Muslim family counselling, Islamic education policy, and community daʿwah programming in rapidly urbanizing Indonesian society.